Hair Growth-Promoting Effect of Resveratrol in Mice, Human Hair Follicles and Dermal Papilla Cells - Zhang Y (Dove Medical Press, 2021)
Yuting Zhang,1,* Chunya Ni,2,* Yan Huang,1,* Yulong Tang,1 Kai Yang,2 Xiangguang Shi,3 Yue Zhang,3 Zheng Li,3 Ji’an Wang,3 Yifei Zhu,3 Haiyang Li,3 Yanyun Ma,1 Jinran Lin,3 Jiucun Wang,1,3,4 Qingmei Liu,3 Wenyu Wu2,3,5 1State Key Laboratory of Genetic Engineering, Collaborative Innovation Center for Genetics and Development, School of Life Sciences, Fudan University, Shanghai, People’s Republic of China; 2Department of Dermatology, Jing’an District Central Hospital, Shanghai, People’s Republic of China; 3Department of Dermatology, Huashan Hospital, Fudan University, Shanghai, People’s Republic of China; 4Institute of Rheumatology, Immunology and Allergy, Fudan University, Shanghai, People’s Republic of China; 5Academy for Engineering and Technology, Fudan University, Shanghai, People’s Republic of China*These authors contributed equally to this workCorrespondence: Qingmei Liu; Wenyu WuDepartment of Dermatology, Huashan Hospital, Fudan University, 12 Mid-Wulumuqi Road, Shanghai, 200040, People’s Republic of ChinaTel +86-21-52889999Fax +86-21-52887782Email liuqing.mei@huashan.org.cn; wuwenyu@huashan.org.cnBackground: Oxidative damage has been found in various types of hair loss. As a polyphenolic phytoalexin, resveratrol (RSV) is known as an antioxidant, anti-inflammatory and anti-apoptotic agent.Objective: Thus, we aim to examine the effects of RSV on hair growth.Methods: In vivo C57BL/6 mice were used to evaluate the effects of RSV on hair cycle, hair length, skin thickness, hair follicle diameter, hair cycle score and the percentage of hair cycle stage. Then hair shaft length and hair cycle were evaluated by human hair follicles (HFs) ex vivo. The proliferative activities of human dermal papilla cells (hDPCs) cultured in vitro with RSV were assessed using RTCA. The ability of RSV to protect hDPCs against H2O2-induced oxidative damage is examined by a ROS assay kit.Results: Topical application of RSV significantly promoted hair growth and stimulated the transition of hair cycle from telogen into the anagen phase on shaved C57BL/6 mice. Ex vivo experiments showed that RSV increased the hair shaft length of HFs and delayed the entry into catagen. In vitro experiments indicated that RSV proliferated hDPCs and prevented hDPCs from oxidative damage caused by H2O2.Conclusion: RSV can promote hair growth and may be a potential candidate for the treatment of hair loss.Keywords: resveratrol, hair growth, hair cycle, hair follicle, dermal papilla cells